Design and Experimental Validation of the Versatile Voltage Conveyor‐Based Novel Mixed‐Mode Universal Filter Configurations and Quadrature Oscillator - Mohammad Faseehuddin; Sadia Shireen; Orapin Channumsin; Mousumi Bhanja; Worapong Tangsrirat (Journal of Electrical and Computer Engineering, 2025)
In this research, a truly mixed‐mode multi‐input single‐output (MISO) universal filter is designed using a second‐generation voltage conveyor (VCII) and an operational transconductance amplifier (OTA). The filter is designed with three VCIIs, three OTAs, two resistors and two grounded capacitors. It is capable of producing various responses including low‐pass (LP), high‐pass (HP), band‐pass (BP), band‐reject (BR) and all‐pass (AP). The filter can also function in all four possible modes of operation: voltage mode (VM), current mode (CM), trans‐admittance mode (TAM) and trans‐impedance mode (TIM). The merits of the filter comprise (i) no requirement for matching passive component; (ii) use of grounded capacitors; (iii) low‐output impedance in VM and TIM operations; (iv) high‐output impedance in CM and TAM operations; and (v) the capacity to tune the quality factor ( Q ) and the natural angular frequency ( ω o ). A dual‐mode quadrature oscillator is additionally derived from the proposed filter core. The condition for oscillation and the oscillation frequency can be regulated independently. Moreover, a novel VCII‐exclusive mixed‐mode filter topology is developed from the designed filter. A study is performed on the non‐ideal gains and parasitic effects of the circuits. The designed filters and oscillators are validated in the Cadence design suite using a 0.18 μm real CMOS process. The filters are validated at a frequency of 1.59 MHz, and the oscillator is examined at 1.25 MHz at supply voltages of ±0.9 V. The mixed‐mode filter has also been experimentally tested using commercial integrated circuits (ICs), specifically AD844 and LM13700. The theoretical results are found to exhibit a close correlation with the simulated ones.
Keywords: Analog and Mixed-Signal Circuit Design; Radio Frequency Integrated Circuit Design; Advancements in PLL and VCO Technologies